Impact of brassinosteroid mimic on photosynthesis, carbohydrate content and rice seed set at reproductive stage under heat stress - Sonjaroon, Weerasin; Jutamanee, Kanapol; Khamsuk, Ornusa; Thussagunpanit, Jutiporn; Kaveeta, Lily; Suksamrarn, Apichart (Agriculture and Natural Resources, 2018)
Brassinosteroid mimics have been shown to increase photosynthesis in plants and alleviate the effects of heat stress. 7,8-Dihydro-8a-20-hydroxyecdysone (αDHECD) is a brassinosteroid mimic, but there has been no reporting on the mechanism of αDHECD against heat stress. Therefore, the effect of αDHECD was investigated on photosynthesis and seed set in rice subjected to heat stress. In this experiment, rice plants were applied with water or 0.0001 mM αDHECD by foliar application before being subjected to heat stress during the reproductive growth stage. Then, plants were exposed to either a normal temperature regime of 30/26 °C day/night or to a high temperature regime of 40/30 °C day/night for 7 d. The results showed that αDHECD increased the net photosynthetic rate under the normal temperature regime. Under heat stress, αDHECD enhanced the net photosynthetic rate, stomatal conductance, transpiration rate and stomatal limitation, while decreasing the intercellular CO2 concentration and efficiency of water utilization. αDHECD also increased the total soluble sugar content in rice leaves under the normal and high temperature treatments. The application of αDHECD also increased seed setting, seed weight and the sugar and starch contents in the straw and seed under heat stress. The results indicated that αDHECD is a brassinosteroid mimic that enhances photosynthetic performance, increases the carbohydrate contents in the straw and seed and improves rice seed set under high temperatures when it is applied in the reproductive growth stage.